Collaboration between speech and language therapists and school staff when working with graphic symbols - Pampoulou, Eliada (My University, 2016)
A growing number of research projects show that graphic symbols with linguistic characteristics are one of the tools that professionals use in order to support pupils in inclusive school settings. However, there is scant literature investigating the collaboration between professionals who use these symbols in these settings and, hence, this research article is aimed at exploring the factors that promote or hinder collaboration between speech and language therapists and school staff who use graphic symbols. The phenomenology of pedagogy was the methodological framework used in the research and for this reason, semi-structured interviews, close observations and the researcher keeping a reflective journal were the main instruments that were used during data collection. Based on a survey conducted in 100 schools in two different geographical areas in England and in Cyprus, four schools were selected in which nine professionals in total participated in the research. The findings show that collaboration among school staff was influenced by the shared understanding the participants had about their own and others' professional roles and goals, the availability of time for meeting as well as the support they received from school staff in positions of authority.
Keywords: Collaboration; Graphic symbols; Inclusion; Phenomenology; School staff; Speech and language therapists